Descripción de las fases fenológicas desde floración hasta cosecha del cultivo de Lupino (Lupinus mutabilis, Sweet), de las variedades INIAP-451 (Guaranguito), INIAP-450 (Andino) y su tiempo fisiológico. Salache – Cotopaxi 2021-2022 - Choloquinga Ayala, José Cruz (2022)
The purpose of this research is to determine the phenological phases from flowering to harvest of the Lupin crop (Guaranguito and Andino varieties) and its physiological time measured in thermal units. The research project was carried out at the CEASA Campus, Eloy Alfaro parish, Canton Latacunga, 2021. The objectives of this study were: To describe the development of the varieties under study through physiological time from flowering to harvest and to determine the thermal units in the Lupin varieties in their phenological phases from flowering to harvest. The morphological indicators evaluated were: plant height, flower bud length, flower bud diameter, flowering percentage, green and dry grain yield, the following data were obtained for height INIAP-450 Andino 162.23 and INIAP 451-Guaranguito 159.91, flower bud length INIAP-450 Andino 25.09 and INIAP 451-Guaranguito 21.88, flower bud diameter INIAP-450 Andino 51.11 and INIAP 451-Guaranguito 53. 36, flowering percentage INIAP-450 Andino 15% and INIAP 451-Guaranguito 5%, green grain yield INIAP-450 Andino weight with pod 255.48, weight without pod 101.24, number of pods 52.51 and INIAP 451-Guaranguito weight with pod 349.95, weight without pod 60. 3, number of pods 62.61 and dry grain yield INIAP-450 Andino weight with pods 97.61, weight without pods 59.19, number of pods 57.68 and INIAP 451-Guaranguito weight with pods 120.05, weight without pods 60.3, number of pods 58.3. Data were taken from day 109 after planting, until day 180-200, plant height and other data were taken from day 109, for yield data were taken in 116 days and dry grain yield data were taken in 190 for Guaranguito and 200 for Andean. For the calculation of degree days of development, temperature data were taken from the CEASA Campus weather station, with a frequency of 3 times a day